PELATIHAN PENYUSUNAN LAPORAN KEUANGAN YANG EFEKTIF UNTUK USAHA BUDI DAYA MADU LEBAH TANPA SENGAT/GALO-GALO (TRIGONA SP) PADA CV SHAHABAT MADU DI KOTA PADANG - Mike Kusuma Dewi; Elsa Meirina; Renil Septiano (LPPM Universitas Bina Bangsa, 2022)
The financial report is a file recording money, where the report contains all kinds of transactions involving money, both purchase and sale and credit transactions. This report is made in a certain period, for example every month or every year. It depends on each company's policy. Financial reports are made to determine the company's financial condition. Therefore, the financial manager must make it precise and accurate, and be responsible for presenting the reports that have been made in detail to the superiors. Based on this, we from the Lecturer team do service in the Kuranji Padang area for the business of cultivating stingless bee honey / Galo-galo which is also managed by CV Shahabat Madu. this activity was carried out for approximately 3 hours, by conducting a question-and-answer session between the lecturer team and the honey bee managers regarding how to carry out the recording of financial transactions and financial reports